RIBOSOME CRYSTALLIZATION IN CHICKEN EMBRYOS : II. Conditions for the Formation of Ribosome Tetramers In Vivo - Morimoto, T. (The Rockefeller University Press, 1972)
Slow cooling of fertilized chicken eggs permits the elongation and termination of nascen(t) polypeptides in the polysomes but prevents the initiation of new protein chains. This leads to polysome disaggregation during the first 30 min of cooling, and to the formation, of a pool of inactive ribosomes prone to crystallization. After 2 hr these ribosomes began to form tetramers, which do not contain any labeled proteins synthesized during cooling. If protein synthesis is inhibited by cycloheximide, added to eggs before cooling, tetramer formation in the embryos is prevented. Puromycin, on the other hand, leads to polysome disassembly and does not prevent tetramer formation. Rapid cooling of explanted embryos after short incubation at 37°C, with or without cycloheximide, largely prevents polysome disaggregation and the formation of tetramers. On the other hand, the addition of puromycin to explanted embryos promotes tetramer formation after rapid cooling. When cooled eggs are rewarmed, tetramers are disassembled into monomers, even if protein synthesis is inhibited. When those embryos were rapidly recooled tetramers reformed spontaneously from tetramer-derived monomers, even in the presence of cycloheximide. We conclude that the formation of tetramers at low temperature is an inherent property of the normal ribosomes.